Quality improvement in emergency medical services: shared experiences of South Africa with pre-war Ukraine - Christopher, Lloyd; Naicker, Visvanathan; Naidoo, Navindhra (Technology audit and production reserves, 2023)
In the Republic of South Africa (RSA) healthcare quality including Emergency Medical Services (EMS) is impaired by scarce resources and variable governance and management. The National Health Quality Improvement Plan (NHQIP) seeks to transform health care quality through standards setting. In RSA EMS managers monitor and adjust quality to comply with the Regulations Relating to Standards for EMS. EMS management training is deficient, and it is unknown how prepared they are to meet quality standards. Object of research: How can the knowledge, attitude, and practice (KAP) of EMS managers be transformed to comply with the standards regulations for EMS. A mixed methods explanatory sequential design was conducted in two phases. Phase one consisted of a KAP quantitative survey (n=352). Phase two included the non-participant observations (N-PO) at country-wide management workshops (n=7 provinces) and interviews (n=11) with key informants/power brokers. The data was analyzed to develop themes to deepen the understanding of the survey data. Fragmentation of EMS into districts; ineffective workforce management; poor fleet management; poorly trained dispatchers, underutilization of information communication technology and vehicle tracking are factors that compromises the access, safety and contribute to ineffective and inefficient EMS. The World Health Organization (2020) report on EMS in Ukraine identified similar challenges. EMS quality challenges in RSA are not unique, and sharing common challenges, experiences and solutions may benefit EMS organizations in other developing countries such as Ukraine.